ANALISIS MODEL DINAMIS DAMPAK INFLASI TERHADAP SEKTOR PERTANIAN INDONESIA TAHUN - Rahmat Hadi Nugroho (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2006)
Agriculture sector have positive growth while national growth have been negative, and its function in GDP still significant when economic crisis occurred. For more accurated analysis, economic growth can be devide in to sectoral activities. Using macro economic theories through relationship between prices and real growth would be faced agriculture real growth through consumer’s price index, general prices in the agriculture sector within prices received and prices paid, and agriculture wage as an indicator for supply aggregate and dummy variable to vanish effect of economic crisis in the model. This study use time series data. To solve spurious regression, we use error correction model. The conclusion are: first, factors that influenced GDP of agriculture sector are long run variables of consumer’s price index, general prices in the agriculture sector within prices received and prices paid, and agriculture wage; second, inflation is faster than agriculture growth, that must be followed by fiscal and monetary policy to affect supply aggregate, to increase productivity of agriculture sector, for instance by increasing technology in to agriculture sector, and more qualified human resource with education. Or can be combined between fiscal policy and income policy, withn labor intensive program to develop agriculture project, so government expenditure and agriculture asset increases all at once.